HUBUNGAN KOMPETENSI DIGITAL DAN PENGGUNAAN APLIKASI TUNJANGAN REMUNERASI KINERJA (TRK) JABAR PADA ASN DI SEKRETARIAT DAERAH PROVINSI JAWA BARAT - Karin Aura Nur Utami; Wa Ode Zusnita Muizu (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
This research aims to identify the relationship between Digital Competence and the use of TRK Jabar Application using quantitative methods. Civil Servant in the Electronic Based Government System need to have Digital Competence to follow digital transformation, especially in the use of TRK Jabar Application in West Java Province Regional Secretariat. The total sample in this study was 175 respondents who were analyzed using the Spearman correlation test method with the help of SPSS version 25 software. The research results show that digital employee competency is included in the Good category and the use of TRK Jabar Application is also in the Good category. Apart from that, employee digital competence is related to the use of TRK Jabar Application with a correlation coefficient value (0.703) which describes the strength of the position relationship so that if there is a change in digital competence, the use of TRK Jabar Application will increase. also tends to change. Apart from that, with a significance value of 0.000 < 0.005 and an r value > 0, these variables are positively linearly related so that if digital competence increases then the use of TRK Jabar Application will also increase, as will if it decreases. This research results that Digital Competence has a significant and positive correlation with the use of the West Java TRK Application.